Millennial loyalty in Halal tourism: a destination-based analysis - Dwi Suhartanto; Dean, David; Nono Wibisono; Carol Y. Lu; Hanudin Amin (Taylor and Francis Ltd., 2021)
This study seeks the answer to the proposed questions of past Halal tourism studies, namely how does loyalty form for Millennial Muslim tourists when they visit domestic or international destinations. The data for this study were collected from 432 Indonesian Muslim Millennials. Using partial least squares structural equation modelling, this research shows that Halal experience and attraction experience influence the perceived value, satisfaction, and loyalty of Muslim Millennial tourists. While Halal experience is considered to be an important factor in determining Millennial Muslim satisfaction when visiting domestic destinations, Halal experience is not considered as important when visiting international destinations. Further, perceived value, satisfaction and loyalty are more influenced by experience with tourism attractions than by Halal experience when visiting either domestic or international destinations.